Motivation In Maintaining Dental and Oral Hygiene Using Dental Maze Media (Students of Class 4A and 4B SDN Pandanwangi 1 Malang) - Ansory, Nisrina Salsabila; Mahirawatie, Ida Chairanna; Marjianto, Agus (SURABAYA DENTAL THERAPIST JOURNAL, 2025)
Poor dental and oral hygiene remains a prevalent issue among elementary school children. Problem statement: A preliminary survey of 10 students at SDN Pandanwangi 1 Malang revealed an average debris index of 2.0, which falls under the "poor" category. Method: This descriptive study involved 55 respondents. Data were collected using likert scale questionnaires to assess both intrinsic and extrinsic motivation regarding dental and oral hygiene maintenance. The analysis was conducted by calculating response averages, converting them into percentages, and presenting the results in tabular form. Scientific finding results: The findings indicate that after using dental maze media, students intrinsic motivation for maintaining dental and oral hygiene reached 94%, while extrinsic motivation scored 90%. Conclusion: Intrinsic and extrinsic motivation of students after using the dental maze media is categorized as very strong.